Few-layered Ti3C2 MXene-coated Ti–6Al–4V composite powder for high-performance Ti matrix composite. (August 2022) - Wang, L.; Liu, Z.Q.; Li, S.F.; Yang, Y.F.; Misra, R.D.K.; Li, J.; Ye, D.; Cui, J.Y.; Gan, X.M.; Tian, Z.J.
Abstract: A few-layered Ti3 C2 MXene-coated Ti–6Al–4V composite powder was developed via powder surface modification by using fluidization technology. The obtained MXene coating demonstrated the advantages of uniform dispersion, high purity and good thermal stability. Also, the coating enabled the massive retention and uniform distribution of MXene in the sintered composite. Compared to the bare Ti–6Al–4V alloy, the yield strength of MXene/Ti–6Al–4V composite was increased from 895 to 1297 MPa, while maintaining the similar strain. The thermal conductivity of composite was approximately four-fold compared to that of Ti–6Al–4V alloy, which is attributed to the intrinsically high thermal conductivity and the uniform distribution characteristics of the remained Ti3 C2 MXene in the composite. Graphical abstract: Image 1 Highlights: A uniform few-layered MXene/Ti–6Al–4V composite powder was initially developed. The MXene had advantages of uniform dispersion, high purity and thermal stability. MXene was retained in Ti matrix after sintering and increased the strength by ∼45%. The thermal conductivity of Ti–6Al–4V alloy was improved by a factor of ∼ four.